Trajectories of interparental conflict and children's emotional-behavioural functioning at 10-11 years: an Australian population-based study - Fogarty, Alison; Feinberg, Mark; Gartland, Deirdre; Cooklin, Amanda; Giallo, Rebecca; Seymour, Monique; Wood, Catherine; Brown, Stephanie; Christensen, Daniel (My University, 2021)
Interparental conflict (IPC) has the potential to adversely affect children's social, emotional, and behavioural functioning. The overall objective of this study was to investigate the relationship between both the severity and chronicity of IPC across early and middle childhood and children's emotional-behavioural functioning at 10-11 years. Specifically, we aimed to: (1) identify distinct trajectories of IPC spanning 10-11 years since birth of the study child as reported by mothers, and (2) examine the emotional-behavioural functioning of children exposed to the identified IPC trajectories. Drawing from a nationally representative longitudinal study of Australian families (N = 4875), four distinct trajectories of IPC were identified: (1) consistently low exposure to IPC over time, (2) persistently elevated exposure to IPC, (3) increasing IPC exposure over time, and (4) decreasing IPC exposure over time. Children exposed to trajectories with high IPC at any point during the study period were reported by their mothers to be experiencing more emotional-behavioural difficulties than children exposed to low IPC over time. Based on teacher report, there were no differences in emotional-behavioural functioning of children exposed to the different patterns of IPC. Our findings reinforce that high parental conflict at any point in a child's life is a form of adversity that can have adverse consequences for their mental health, and that early interventions for parents and caregivers experiencing high IPC are critical.
European Child and Adolescent Psychiatry
Keywords: Adolescents and youth; Childhood and child development; Families and relationships; Health and wellbeing